PELATIHAN PENGENALAN JENIS-JENIS PENCEMARAN UDARA SEBAGAI USAHA PENINGKATAN KESADARAN MASYARAKAT - Sujarta, Puguh; Sufaati , Supeni; Surbakti , Suriani Br.; Farmawaty, Farmawaty; Purnamasari , Vita; Omega , Charisma Puspa (LPPM Uncen, 2024)
The impact of development has risks for society, one of the impacts of development is the emergence or occurrence of environmental pollution. The objectives of the service activities: (1) introduce a training program to recognize types of air pollution; (2) through service it can produce output in the form of a national service journal. This activity was held on July 20, 2023 at SMA Negeri 2 Skanto Keerom. The target audience involved in this activity are high school students. The selection of the target audience is based on the tasks and obligations of students to build Adiwiyata High School that loves the environment. The methods used in the implementation of this activity are lectures, simulations and practice on how to harvest and use it. The conclusion is that: (1) Participants are very enthusiastic about participating in service activities and understand air pollution, its types and impacts; (2) based on the evaluation results, it shows that the level of understanding of the participants is quite good when seen from the percentage of all participants' opinions.